Correlation of HLA-A and HLA-B/C expression with PD-1 and PD-L1 expression in patients with metastatic breast cancer as a potential prognosticator of favorable survival - Goerdt, Lukas; Stefanovic, Aleksandra; Wirtz, Ralph; Karic, Uros; Kohler, Maximilian; Deutsch, Thomas M.; Schneeweiss, Andreas; Sütterlin, Marc; Stefanovic, Stefan; Hofmann, Jan; Wallwiener, Markus (In vivo, 2025)
Background/Aim: Class 1 human leukocyte antigen (HLA) ensures that cytotoxic T lymphocytes (CTLs) attack tumor cells. As part of tumor de-differentiation, the expression of HLA on the tumor cell surface may decrease, which can facilitate tumor growth. Therefore, reduced expression of HLA is generally negatively associated with overall survival (OS). The reverse is true for programmed cell death protein (PD-1) and programmed death ligand 1 (PD-L1). The presence of PD-1 and PD-L1 on the surface of cancer cells inhibits immune defense mechanisms against cancer cells. Therefore, one would expect that increased PD-1/PDL-1 expression would result in decreased 5-year survival. The aim of this study was to correlate the expression levels of HLA-A and HLA-B/C with the expression levels of PD-1 and PDL-1 to evaluate the reliability of their prediction of 5-year OS. - Materials and Methods: This study retrospectively examined patients upon the start of a new therapy line for metastatic breast cancer (MBC). The pilot cohort fulfilling very demanding inclusion criteria consisted of 34 patients. The diagnostics were primarily carried out using RT-qPCR. - Results: The expression of HLA-A, HLA-B/C, PD-1, and PD-L1 is not significantly associated with OS. - Conclusion: This pilot study found no significant association between HLA-A, HLA-B/C, PD-1, or PD-L1 expression and OS in MBC, indicating limited prognostic value for these biomarkers in this cohort.